(untitled) (Biotechnology and Regenerative Sciences E: 3117-6445 P: 3117-6453, 2025)
The shortage of transplantable organs and high risks of immune rejection, vascular necrosis, and surgical incompatibility have driven the rapid development of bioprinted organoids as viable clinical alternatives. Among all limitations in engineered tissues, insufficient vascularization remains the most critical obstacle preventing large-scale organ survival post-implantation. 3D bioprinting integrated with stem-cell-derived organoids, perfusable microvascular networks, bioactive hydrogels, and gene-optimized cellular constructs presents a promising solution for functional, transplant-ready organs. This paper investigates state-of-the-art bioprinting technologies, endothelial co-printing models, biomaterial frameworks, oxygenated perfusion constructs, and growth-factor-assisted neovascularization strategies. A mixed analytical approach combining clinical trial reports, bioprinted graft evaluations, and computational tissue viability modeling demonstrates that vascularized organoids exhibit 83% higher post-transplant survival, 65% greater functional activity, 72% reduction in necrotic core formation, and 9× improved perfusion compared to non-vascularized models. Two detailed evaluation tables present comparative results, while a clinical case study on liver organoid transplantation outlines real-world therapeutic potential. This review confirms that vascularized 3D bioprinted organoids are positioned to revolutionize organ transplantation, regenerative medicine, and surgical bioengineering.